Strategi Badan Penanggulangan Bencana Daerah dalam Penanggulangan Bencana Alam Banjir di Kabupaten Karimun Tahun 2023 - Sudeno Atmaja; Bismar Arianto; Eki Darmawan (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
The flood problem should be a serious concern for all parties, both the community and the local government in Karimun Regency. This study aims to determine the strategy of the Karimun Regency BPBD in post-flood disaster management in Karimun Regency and to determine the obstacles faced by BPBD in post-flood disaster management in Karimun Regency. The research method that will be used in this study is the Qualitative Descriptive research method, data collection techniques are observation, interviews and documentation. This study uses Kooten's strategy theory, namely organizational, program, resource, institutional strategies. The findings obtained by the researcher, (1) the organizational strategy carried out by the Karimun Regency BPBD, namely having carried out several activities such as recovery, rehabilitation and reconstruction even though these activities have been running, has been quite effective. (2) the program strategy carried out by BPBD has not been able to run the program effectively, because there are 2 programs that are still in the planning stage. (3) the resource strategy, which is provided is not effective enough, because BPBD itself still lacks human resources and facilities and infrastructure. (4) institutional strategies are quite effective, BPBD has a work plan, namely coordination between agencies, joint evacuation and early warning systems and strengthening institutional capacity.